ANALYSIS OF THE INTEGRATION OF THE DINIYAH CURRICULUM AND THE INDEPENDENT CURRICULUM IN BOOK-BASED RELIGIOUS LEARNING AT PKBM AL WAFA ELEMENTARY SCHOOL, SIDOARJO - Mei Kalimatusyaro; Dwi Qurrota ‘Ayun; Muhammad Irfan Firdani; Nurul Hidayati; Rifdah Rusdania; Witris Salami (Institut Agama Islam Uluwiyah Mojokerto, 2025)
This study aims to analyze the integration of the Diniyah Curriculum and the Merdeka Curriculum in book-based religious learning at PKBM Al Wafa Elementary School. The integration is essential because the institution maintains its religious educational identity through classical Islamic texts while simultaneously adhering to national standards required by the Merdeka Curriculum. This research employs a qualitative approach using a case study design to explore the implementation process, teaching strategies, and supporting and inhibiting factors of curriculum integration. Data were collected through observations, interviews, and document analysis. The findings reveal that integration is carried out by aligning classical texts such as Akhlakul Banin and Khulashoh with the learning outcomes of the Merdeka Curriculum. Teachers adopt gradual instructional methods, including demonstrations, text reading, and vocabulary interpretation, supported by contextual activities that promote meaningful learning experiences. Key supporting factors include the school’s strong diniyah culture, parental involvement, and teacher competence. Challenges arise from students’ young age and varying levels of learning motivation. Overall, the integration process is effective and contributes positively to students’ understanding of moral values and the strengthening of religious character formation.